The impact of merged organiztions culture on enterprise success - Vaitkūnaitė, Vida (Business: Theory and Practice, 2006)
Failures of enterprises forced scientists to pay attention to intangible side of organization. They note that organizational culture can cause success or failure. Most scientists analyzed this influence in non-merged organizations. However, enterprises merge more often, but there are few investigations and they are not comprehensive. In this article the author discusses the concept of organizational culture, its impact on success, discloses the problems of culture analysis of merged companies and proposes the outline of research methodology of culture impact on success. It is proposed to combine quantitative and qualitative research methods, to distribute research into three periods and to separate companies into separate unit, not analyzing them as a single one.Article in Lithuanian.Susijungusių organizacijų kultūrų poveikis įmonės sėkmeiSantrauka. Įmonių nesėkmės privertė mokslininkus atkreipti dėmesį į nematerialius organizacijos dalykus. Pastebėta, kad sėkmę ar nesėkmes gali lemti organizacijos kultūra. Daugiausia tyrėjų šį poveikį analizavo nesusijungusiose organizacijose. Tačiau susijungiančių įmonių vis daugėja, o tyrimų yra mažai ir jie nėra išsamūs. Siame straipsnyje aptariama kultūros samprata, poveikis sėkmei, atskleidžiamos susijungusių įmonių kultūrų analizės problemos ir pateikiami kultūros poveikio sėkmei tyrimo metodikos metmenys: siūloma derinti kiekybinius ir kokybinius tyrimo metodus, tyrimą suskirstyti į tris periodus ir įmones analizuoti kaip atskirus vienetus, o ne kaip vientisą junginį.Pagrindiniai žodžiai: organizacijos kultūra, susijungusios įmonės, įmonių sėkmė, tyrimo metodika.